Respostas
respondido por:
1
Resposta:
3 • ( x - 1 ) = 6
3x - 3 = 6
3x = 6 + 3
3x = 9
x = 9/3
x = 3
prova real:
x • ( x - 1 ) = 6
3 • ( 3 - 1 ) = 6
3 • 2 = 6
6 = 6
respondido por:
0
Resposta:
resposta: x = 3
Explicação passo a passo:
Resolvendo equação do primeiro grau:
Saiba mais, acessando:
https://brainly.com.br/tarefa/43297090
https://brainly.com.br/tarefa/47984280
https://brainly.com.br/tarefa/46934741
https://brainly.com.br/tarefa/44774827
https://brainly.com.br/tarefa/41888605
https://brainly.com.br/tarefa/40290201
https://brainly.com.br/tarefa/39221005
https://brainly.com.br/tarefa/41833178
https://brainly.com.br/tarefa/49281853
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás